Analysis of the Impact of Meteorological Parameters Over the Main Stage of Rice Cultivation in Mazandaran Province - Anahita Kheirkhah; Gholam Ali Kamali; Amirhossein Meshkvati; Hossein Babazadeh; Ebrahim Asadi Oskouei (Nīvār)
It has been tried to investigate and study the fluctuations of different meteorological parameters at different probability levels in the important stages of the agricultural calendar. To conduct this study, first, the traditional agricultural calendar was prepared through the reports of the Amol Rice Research Center and with the help of interviews with rice farmers and the cooperation of rice agricultural experts. Among the various stages in the agricultural calendar, 5 stages were selected as the main stages including: land preparation, treasury, transplanting, flowering and ripening of seeds and harvesting. Then, the data of temperature, precipitation, humidity, wind speed, sunshine hours and surface temperature in 9 weather stations as representative of the main rice growing areas in the province for the statistical period of 2005 to 2020 were received from the Meteorological Organization. . According to the agricultural calendar and the time frames for the 5 mentioned stages and the appropriate thresholds and weather conditions at that time, the compatibility of the favorable conditions for rice cultivation operations in different stages with the actual conditions of investigation and the expected values ​​of each parameter in each period It was calculated at different probability levels. The results show the amount and possible thresholds of the effective parameters in the 5 stages of the rice cultivation calendar. The results showed that the average temperature in the five mentioned stages is 12.8, 14.3, 18.7, 20.7 and 31.4 degrees Celsius, respectively, which is within the optimal thermal threshold range for all agricultural operations.